The Influence of Organizational Climate and Visionary Leadership on Job Satisfaction and Their Impact on Teacher Performance at SIT Nurul Ilmi Jambi - Sai'in Muhammad (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
Sai’in Master Of Education Management At Jambi University dewisaiinfajar@gmail.com This research is a survey research type with a quantitative approach which is done in schools under the SIT Nurul Ilmi Jambi Foundation. This study purposed to determine whether or there is not an influence of organizational climate and visionary leadership on job satisfaction and its impact on teacher performance at SIT Nurul Ilmi Jambi. The data collection method in this study was a questionnaire. The sampling technique used is the census method or the saturated method. The population that became the object of the study were teachers of Kindergarten 1 and 2, SD 1 and 2, SMP 1 and 2 and SMA in SIT Nurul Ilmi Jambi with a total of 190 permanent teachers from seven schools. Hypothesis testing was carried out by linear regression analysis for hypotheses 1, 2, 3, 4 and 5, path analysis and Sobel test for hypotheses 6 and 7 through the SPSS 24.0 for windows program. Based on the research framework, hypotheses were obtained in this study, are (1) organizational climate has a direct positive influence on job satisfaction of SIT Nurul Ilmi Jambi teachers; (2) Visionary leadership has a direct positive influence on job satisfaction at SIT Nurul Ilmi Jambi; (3) Organizational climate has a direct positive influence on the performance of SIT Nurul Ilmi Jambi teachers; (4) Visionary leadership has a direct positive influence on the performance of SIT Nurul Ilmi Jambi teachers; (5) Job satisfaction has a direct positive effect on the performance of SIT Nurul Ilmi Jambi teachers; (6) Organizational climate through job satisfaction has an indirect positive influence on the performance of SIT Nurul Ilmi Jambi teachers; (7) Visionary leadership through job satisfaction has an indirect positive influence on the performance of SIT Nurul Ilmi Jambi teachers. Keywords: Organizational Climate, Visionary Leadership, Job Satisfaction, Teacher Performance